2015
DOI: 10.1002/pro.2741
|View full text |Cite
|
Sign up to set email alerts
|

A new method for detection of tumor driver‐dependent changes of protein sialylation in a colon cancer cell line reveals nectin‐3 as TGFBR2 target

Abstract: Protein-linked glycans play key roles in cell differentiation, cell-cell interactions, cell growth, adhesion and immune response. Aberrant glycosylation is a characteristic feature of tumor cells and is involved in tumor growth, escape from apoptosis, metastasis formation, and resistance to therapy. It can serve as cancer biomarker and treatment target. To enable comprehensive screening for the impact of tumor driving mutations in colorectal cancer cells we present a method for specific analysis of tumor drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…The TGFBR2 genes possess a stretch of 10 adenine residues, which frequently undergo frameshift mutations in MSI CRC, leading to TGFBR2 inactivation, a crucial mutational step for CRC progression. In the CRC cell line HCT116 expressing the biallelic inactivation of TGFBR2, the reconstitution with a wild type TGFBR2 gene leads to altered sialylation of a variety of glycoproteins [ 163 , 164 ], without any change in the expression of sialyltransferases [ 164 ], suggesting a relationship between sialylation and a classical mutational step in CRC. β1,6-branching is involved in the pathogenesis of liver disease through TGFB signaling.…”
Section: How Glycosylation Modulates the Activity Of Specific Recementioning
confidence: 99%
“…The TGFBR2 genes possess a stretch of 10 adenine residues, which frequently undergo frameshift mutations in MSI CRC, leading to TGFBR2 inactivation, a crucial mutational step for CRC progression. In the CRC cell line HCT116 expressing the biallelic inactivation of TGFBR2, the reconstitution with a wild type TGFBR2 gene leads to altered sialylation of a variety of glycoproteins [ 163 , 164 ], without any change in the expression of sialyltransferases [ 164 ], suggesting a relationship between sialylation and a classical mutational step in CRC. β1,6-branching is involved in the pathogenesis of liver disease through TGFB signaling.…”
Section: How Glycosylation Modulates the Activity Of Specific Recementioning
confidence: 99%
“…There are also multiple known protein receptors for TcdB. All of the protein targets, NECTIN3 (19), CSPG4 (18, 20), and FZD1/2/7 (20, 21), are glycoproteins that express a range of different glycosylations, including glycosaminoglycans (chondroitin) (18, 20) and complex N-linked glycans (31, 32). A recent study by Chen et al demonstrated the structure of a region of TcdB (TcdB-FZD binding domain [FBD]) responsible for the interaction with FZD proteins outside the tested region of ToxB-B2 (21).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the downstream effects and modifications identified in the EV cargo can be assigned specifically to the TGFBR2 expression status of MSI cells. For example, our previous studies showed that the reconstituted expression of TGFBR2 alters the glycophenotype of MSI tumor cells (15,32,33), and tumor driver-induced glycome changes have been linked to TGFBR2-regulated genes (34). Additionally, the reconstituted expression of TGFBR2 can cause differential de novo protein expression (35).…”
Section: Discussionmentioning
confidence: 99%